Analisis Yuridis Tindak Pidana Penyebaran Konten Asusila Berdasarkan Undang-Undang No. 19 Tahun 2016 Tentang Informasi Dan Transaksi Elektronik - Satria Bagus Santoso (Albayan Journal of Islam and Muslim Societies, 2024)
Criminal acts of indecency involving the dissemination of indecent photos through social media have a negative impact on society. The research questions include: (1) how are criminal acts of indecency involving the distribution of indecent photos through social media accounts regulated by law; (2) how are perpetrators held accountable; and (3) how do judges consider criminal sanctions against perpetrators, as in Decision Number 483/Pid.B/2019/PN.Amb. This research uses a descriptive literature review method and a normative legal approach analyzed qualitatively. Legal regulations regarding the distribution of indecent photos through social media are contained in the Criminal Code, Law Number 44 of 2008 concerning Pornography, and Article 27 paragraph (1) in conjunction with Article 45 paragraph (1) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning ITE. The perpetrator's punishment in the verdict was 3 (three) years imprisonment and a fine of IDR 1,000,000,000, with a subsidiary penalty of 2 (two) months imprisonment. The panel of judges found all elements of the criminal offense proven based on evidence, witness testimony, and the defendant's statements. No justifying or exculpatory reasons were found, so the defendant's actions were legally accountable.